The Effect of Product Quality, Price, and Promotion toward Students’ Purchase Decision for Telkomsel Products - Vincencia, Michel; Christiani, Natalia (Review of Management and Entrepreneurship, 2021)
This study aims to test the effect of product quality, price, and promotion on purchasing decisions. This research specifically focuses on Universitas Ciputra Surabaya students majoring in International Business Management (BMI). This study uses quantitative methods with a total response of 105 students collected from online questionnaires using a 5-point Likert scale measurement. Data were analyzed using SPSS software. The results of this study concluded that product quality did not have a significant effect on student purchasing decisions at Universitas Ciputra Surabaya. Meanwhile, price and promotion significantly influence student purchasing decisions at Universitas Ciputra Surabaya. The results of this research show that both Price (Sig. value = 0.006) and Promotion (Sig. value = 0.002) significantly affects purchase decision, while Product Quality (Sig. value = 0.058) does not have significant influence toward purchase decision. Moreover, the study found that there is a positive relationship between Product Quality, Price, and Promotion toward students' purchase decision for Telkomsel products with the degree of independent variable explaining the effect of Telkomsel product purchasing decisions by 47.3%.